An Analysis Of Classroom Interaction In Teaching EFL Of Students With Dissabilities (Autism) At SLB C Singaraja - ., Ni Luh Ika Ayu Pertiwi; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., I Putu Ngurah Wage M, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Tujuan dari penelitian ini adalah untuk mendeskripsikan 1) Tipe interaksi kelas apa yang digunakan oleh guru dan siswa selama proses belajar dan mengajar di SLB C Singaraja, 2) Kategori interaksi kelas yang mana yang paling sering dilakukan di kelas saat belajar bahasa inggris untuk siswa yang berkebutuhan khusus (autis) di SLB C Singaraja. Penelitian ini menggunakan rancangan qualitative dalam bentuk study kasus. Instrument yang digunakan dalam mengumpulkan data adalah peneliti, kamera, lembar observasi, panduan wawancara. Hasil dari analisis menunjukkan ada 8 tipe Flanders Interaction Analysis Category teori yang terjadi selama interaksi di kelas. Masing-masing presentase keseluruhan pertemuan adalah . Praising or Encouraging 15%, Asking Question 13,9%, Lecturing 7,3%, Giving Direction 30,5% , Criticizing or Justifying Authority 0,004% , Students’- Talk Response 26,7%, Students’ Talk Initiation 2,5% , Silence or Confusion 3,6%. Tipe yang paling banyak ditemukan adalah Giving Direction, sedangkan Criticizing or Justifying Authority adalah tipe yang terjadi paling rendah selama proses belajar dan mengajar.Kata Kunci : Interaksi kelas, Kategori analisis interaksi Flanders teori, Autis This study is aimed at describing (1) types of classroom interaction used by English teacher and students during teaching and learning process in SLB C Singaraja, (2) which category of classroom interaction is most frequently occurs during teaching and learning EFL for students with disabilities (autism) in SLB C Singaraja. The subjects of the study were the teachers and students in grade IX of SLB C Singaraja. This study was qualitative in the form of case study. The instruments used in collecting the data were: the reseacher herself, video camera, observation sheet, and interview guide. The result of the analysis showed that there were eight types of Flanders Interaction Analysis Category theory occurred during the interaction in the class. Respectively, the percentages from the whole meeting were as follows. Praising or Encouraging was 15.02%, Asking Question was 14.25%, Lecturing was 7.38%, Giving Direction was 30.28% , Criticizing or Justifying Authority was 0.51% , Students’- Talk Response was 26.46%, Students’ Talk Initiation was 2.54% , Silence or Confusion was 3.56%. The type of Giving Direction was the most frequently occurred, while Criticizing or Justifying Authority was the lowest frequently occurred during the teaching and learning process. keyword : Classroom interaction, Flanders Interaction Analysis Category theory, Autism